2015
DOI: 10.1177/0363546515599633
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric Knee Flexor Strength and Risk of Hamstring Injuries in Rugby Union

Abstract: Previous HSIs and between-limb imbalance in eccentric knee flexor strength were associated with an increased risk of future HSIs in rugby union. These results support the rationale for reducing imbalance, particularly in players who have suffered a prior HSI, to mitigate the risk of future injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
174
5
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 177 publications
(197 citation statements)
references
References 47 publications
15
174
5
3
Order By: Relevance
“…Previous work has shown that deficits in eccentric knee flexor strength during the performance of the Nordic hamstring exercise are associated with a 4.3 to 4.4-fold increased risk of future hamstring injury in elite Australian rules footballers (Opar et al, 2015a) and professional soccer players (Timmins et al, 2016b), although no such relationship was noted for Rugby players (Bourne et al, 2015). Meanwhile, athletes with a history of ACL injury or HSI display similar eccentric knee flexor weakness and shorter BFLongHead fascicle lengths in previously injured limbs compared to the uninjured contralateral limbs (Opar et al, 2015a;Timmins et al, 2016b).…”
Section: Program Of Researchmentioning
confidence: 96%
See 4 more Smart Citations
“…Previous work has shown that deficits in eccentric knee flexor strength during the performance of the Nordic hamstring exercise are associated with a 4.3 to 4.4-fold increased risk of future hamstring injury in elite Australian rules footballers (Opar et al, 2015a) and professional soccer players (Timmins et al, 2016b), although no such relationship was noted for Rugby players (Bourne et al, 2015). Meanwhile, athletes with a history of ACL injury or HSI display similar eccentric knee flexor weakness and shorter BFLongHead fascicle lengths in previously injured limbs compared to the uninjured contralateral limbs (Opar et al, 2015a;Timmins et al, 2016b).…”
Section: Program Of Researchmentioning
confidence: 96%
“…Late-preseason deficits in eccentric knee flexor strength during the Nordic hamstring exercise are associated with a 4.3 to 4.4-fold increased risk of future hamstring injury in elite Australian rules footballers (Opar et al, 2015a) and professional soccer players (Timmins et al, 2016b), although no such relationship was noted for Rugby players (Bourne et al, 2015).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations